ERGONOMIC ANALYSIS IN A COMPANY OF PLASTIC CONTAINERS MANUFACTURING (Fiep Bulletin - online, 2016)
Ergonomics is the science that seeks to adapt working conditions to the worker. It involves the application of knowledge about the characteristics of the human being to benefit your well being and labor results. All work activities can be seen as a man-machine system within an environment. The objective of this study was to identify the ergonomic working conditions in a manufacturing company of plastic artifacts as methodology Ergonomics Manual Ministry of Labor and Employment within the NR-17 requirements - Ergonomics, through the development of Ergonomics Analysis Work / Ergonomic Report of the jobs of the company's finishing industry. Workers were interviewed with the methodology diagram of Regions Painful (Diagram Corlett) and questionnaire with closed questions about worker profile, environmental conditions, the workplace and the organization of this. The results showed that the biggest complaint this in this environment was spine and lower limbs. By analyzing the results, it is concluded that the implementation of ergonomic improvements is required, guidelines and training for workers, aimed at correcting poor posture and improvement of health conditions while performing their activities.
Keywords: Ergonomic Analysis of Work; Posture; NR-17